Campaign Connections - Samuel Bazzi; Claudio Labanca (Institute of Labor Economics (IZA), 2023)
This paper explores the labor market returns to working on a victorious political campaign. Using unique administrative data from Brazil, we track the earnings and employment of campaign workers before and after close elections spanning nearly 20 years. We identify sizable returns to working for a winning campaign, especially in areas with a large informal sector and for workers connected to newly elected challengers. The returns are concentrated in the public sector, where connected hires are relatively more qualified. Our results suggest a potential upside to patronage as campaign connections create new pathways to public administration for young, high-ability workers.
Keywords: D72; D73; J45; J46; P00; O17; 330; electoral campaigns; labor markets; patronage; political connections